Plant Biology: New Insight into How Roots 'Mask Up' - Monteoliva, Mariela Ines; Bartley, Laura E. (Cell Press, 2021)
Extra- and trans-cellular barriers are essential for root function under even mild stress. New research shows that establishing both the lignin and suberin barriers in the Arabidopsis endodermis requires phenylpropanoid biosynthesis by endodermal cells themselves.